2002
DOI: 10.1238/physica.regular.066a00391
|View full text |Cite
|
Sign up to set email alerts
|

Single Crystal EPR and Optical Studies of Cu(II) Doped Zinc Ammonium Phosphate Hexahydrate: A Case of Rhombic Distortion

Abstract: Single crystal EPR and optical studies of Cu(II) doped ZnNH 4 PO 4 Á6H 2 O (Zinc struvite) have been carried out at room and liquid nitrogen temperatures. The g and A tensors indicate that the impurity has entered the lattice substitutionally.Even though the coordination polyhedron around the host Zn(II) is a compressed octahedron of oxygen atoms of water, the Cu(II) ion has an elongated octahedron corresponding to d x 2 Ày 2 ground state.The optical spectrum shows four bands at 1205, 1095, 833 and 805 nm, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
(11 reference statements)
1
4
1
Order By: Relevance
“…So, in the present study, we report an EPR and optical absorption study of Cu 2+ -doped ZAPH to obtain site symmetry, associated distortion in the lattice and energy level structure, as well as to discuss the nature of the bonding of the metal ion with different ligands. Poonguzhali et al [9,10] have carried out an EPR and optical study of Cu 2+ -doped ZAPH, but they observed a single site in EPR and four bands in optical absorption due to an inappropriate concentration of dopant in the host lattice [8], which, as a result, yielded different EPR and optical absorption spectra compared to the present study. In our study of Cu 2+ -doped ZAPH, two magnetically inequivalent substitutional sites with spin Hamiltonian parameters slightly different from those reported earlier in EPR and five bands instead of four [9,10] in optical absorption are obtained.…”
Section: Introductioncontrasting
confidence: 77%
See 3 more Smart Citations
“…So, in the present study, we report an EPR and optical absorption study of Cu 2+ -doped ZAPH to obtain site symmetry, associated distortion in the lattice and energy level structure, as well as to discuss the nature of the bonding of the metal ion with different ligands. Poonguzhali et al [9,10] have carried out an EPR and optical study of Cu 2+ -doped ZAPH, but they observed a single site in EPR and four bands in optical absorption due to an inappropriate concentration of dopant in the host lattice [8], which, as a result, yielded different EPR and optical absorption spectra compared to the present study. In our study of Cu 2+ -doped ZAPH, two magnetically inequivalent substitutional sites with spin Hamiltonian parameters slightly different from those reported earlier in EPR and five bands instead of four [9,10] in optical absorption are obtained.…”
Section: Introductioncontrasting
confidence: 77%
“…This weak band may be an infrared spectral overtone and/or combination bands [3,30]. Only four bands at 1275, 1115, 840 and 810 nm in optical absorption of Cu 2+ -doped ZAPH at room temperature have been reported by earlier workers [9]. The difference in optical absorption bands in the present case may be due to a difference in the concentration of doping in the host lattice [8].…”
Section: Optical Absorption Analysissupporting
confidence: 44%
See 2 more Smart Citations
“…MPPH crystal belongs to the space group Pmn2 1 , orthorhombic system with unit cell dimensions a = 6.941, b = 6.137, and c = 11.199 Å, and there are two molecules in the unit cell. [16,17] The divalent Mg 2+ is octahedrally coordinated by six water molecules, and [MgO 6 ] 10À octahedron is slightly elongated with orthorhombic (D 2h ) point symmetry, with the Mg-O distances R x ≈ 2.0687 Å and R y ≈ 2.0460 Å for the equitorial bonds and R z1 ≈ 2.1076 Å, R z2 ≈ 2.0940 Å for axial bonds, respectively. [15] When the impurity VO 2+ ) cluster belongs to the obviously tetragonally compressed (and elongated) octahedra in MPPH crystal, characterized by the order of the measured EPR parameters ( g jj < g ⊥ < 2 and jA jj j > jA ⊥ j) for VO 2+ center and ( g jj > g ⊥ > 2 and jA jj j > jA ⊥ j) for Cu 2+ center, respectively.…”
Section: Calculationmentioning
confidence: 99%